Power Allocation Strategies for Distributed Space-Time Codes in Amplify-and-Forward Mode. (14th September 2009) - Maham, Behrouz; Hjørungnes, Are
Abstract : We consider a wireless relay network with Rayleigh fading channels and apply distributed space-time coding (DSTC) in amplify-and-forward (AF) mode. It is assumed that the relays have statistical channel state information (CSI) of the local source-relay channels, while the destination has full instantaneous CSI of the channels. It turns out that, combined with the minimum SNR based power allocation in the relays, AF DSTC results in a new opportunistic relaying scheme, in which the best relay is selected to retransmit the source's signal. Furthermore, we have derived the optimum power allocation between two cooperative transmission phases by maximizing the average received SNR at the destination. Next, assuming M -PSK and M -QAM modulations, we analyze the performance of cooperative diversity wireless networks using AF opportunistic relaying. We also derive an approximate formula for the symbol error rate (SER) of AF DSTC. Assuming the use of full-diversity space-time codes, we derive two power allocation strategies minimizing the approximate SER expressions, for constrained transmit power. Our analytical results have been confirmed by simulation results, using full-rate, full-diversity distributed space-time codes.